Pola Konsumsi Dan Tingkat Ketahanan Pangan Rumah Tangga Miskin Di Desa Sukamaju Kecamatan Mootilango Kabupaten Gorontalo - Harun, Moh. Junaedi; Canon, Syarwani; Akib, Fitri Hadi Yulia (Jurnal Economic Resource, 2025)
This study aims to describe the consumption patterns of poor households and to examine the influence of socio-economic factors on food security in Sukamaju Village. The population consists of 214 beneficiary households of the government food assistance program, from which 70 households were selected using the Slovin formula. Primary data were obtained through structured questionnaires incorporating the Household Food Insecurity Access Scale (HFIAS) to measure food security levels, along with information on consumption patterns, income, education, household size, and food expenditure. Data analysis employed descriptive statistics and ordinal logistic regression using SPSS 22, complemented by Spearman correlation, goodness-of-fit tests, pseudo R-square, and the parallel lines test to assess model adequacy. The results indicate that most households remain food-insecure, particularly within the moderate and severe insecurity categories, reflecting unstable access to food driven by economic pressures. The regression model demonstrates overall significance; however, only food expenditure shows a significant effect on household food security. The high proportion of spending allocated to food emerges as the primary indicator of vulnerability, while consumption patterns, income, education, and household size do not exhibit significant influence. These findings highlight that household food stability is predominantly shaped by economic capacity. Strengthening household income, improving the targeting of food assistance, and enhancing nutrition education and livelihood diversification are essential to reducing food insecurity